(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2016)
The Handbook of the Recognition of Prior Learning: Research into Practice (2014: NIACE) is now available for free download at http://www.learningandwork.org.uk/our-resources/downloadable-publications/handbook-recognition-prior-learning. From the original information sheet about the handbook: "This handbook, organised thematically, consolidates the major research findings of experienced RPL researchers from around the world, identifying future research directions and drawing together evidence-based implications for policy and practice. It is an extremely useful and timely resource as recognition of prior learning continues to develop around the world, especially in the context of lifelong learning policy and national and regional qualifications frameworks. This internationally relevant text will be of particular interest to: • academics, researchers and students in education, policy studies, widening participation, lifelong, adult, continuing, recurrent and initial education and learning • practitioners concerned with RPL policy and actual RPL practice who wish to understand research and its relationship to practice or wanting to research (and improve) their own practice • human resources managers." PLAIO would like to thanks NIACE and the co-editors of the book – Judy Harris, Christine Wihak and Joy Van Kleef – for allowing us to share this resource with our readers.